Investigation of a dislocation in the (110) plane of a cubic crystal/bicrystal - Zhi, Jie Yang. (2008)
In this dissertation, the stress field around a mixed dislocation lying in the (110) plane of a cubic crystal is investigated. It can be concluded that the dislocation line orientation, the elastic anisotropy and the Burgers vector direction all have significant influence on the stress field around the dislocation.